Requirement Model for UUM E-Alumni Club - Amarah, Burhan Daoud As'ad (2008)
The twenty-first century have witnessed several major technological renaissances and many technological achievements as well, which led to a competition among many countries to adapt this trend. Malaysia had improved the infrastructure needed in the information and communication technology area, in order to provide the universities with the new technologies. Therefore the use of the technology becomes available inside the universities. To develop the web-based E-Alumni Club, the study will use the methodology for this study is based on the general methodology in research design, because it is have the logical phases that used to develop a prototype for web-based E-Alumni Club that developed for the Alumni Centre in UUM. To help the student to be closely with graduates student with each other and giving advice and guidance to them by the universities and take advantage of their positions in the service of new graduates and provide feedback to the universities. Finally, the system is tested and the result confirms that the proposed system is successful.